Estimation of the monetary burden of treated human cystic echinococcosis in Pakistan - Basinger, Shawn C.; Khan, Aisha; Ahmed, Haroon; Afzal, Muhammad Sohail; Simsek, Sami; Budke, Christine M. (Elsevier, 2021)
Cystic echinococcosis (CE), caused by the larval stage of Echinococcus granulosus sensu lato tapeworms, continues to be a public health problem in many endemic countries, including Pakistan. Patient level data, including age, sex, and cyst(s) location for surgically managed CE patients for the years 2013-2016 from hospitals located in Punjab and Khyber Pakhtunkhwa provinces were obtained from medical charts. Direct and indirect costs associated with surgically managed CE patients treated in private and public hospitals were then estimated and applied to country-level case numbers estimated through the Global Burden of Disease Study. A total cost of US $4,068,666 (95% CI: US$3,097,684 - US$5,295,702) was estimated for the year 2017, with US$3,951,853 (95% CI: US$2,981,400 - US$5,177,610) attributable to direct diagnosis and treatment-related costs and US$117,137 (95% CI: US$91,841 - US$146, 979) attributable to wage losses during the treatment period. Mean direct cost per patient (US$1,056) was approximately 72% of the country's per capita gross domestic product (GDP). Surgical management continues to be the treatment of choice for CE patients in Pakistan. If physicians were to adhere to World Health Organization Informal Working Group on Echinococcosis (WHO-IWGE) cyst stage specific treatment guidelines, it is likely that the number of surgical interventions would decrease as would treatment costs.
Keywords: Cystic echinococcosis; Pakistan; Cost